2021
DOI: 10.1038/s41467-021-21849-2
|View full text |Cite
|
Sign up to set email alerts
|

Lightning strikes as a major facilitator of prebiotic phosphorus reduction on early Earth

Abstract: When hydrated, phosphides such as the mineral schreibersite, (Fe,Ni)3P, allow for the synthesis of important phosphorus-bearing organic compounds. Such phosphides are common accessory minerals in meteorites; consequently, meteorites are proposed to be a main source of prebiotic reactive phosphorus on early Earth. Here, we propose an alternative source for widespread phosphorus reduction, arguing that lightning strikes on early Earth potentially formed 10–1000 kg of phosphide and 100–10,000 kg of phosphite and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 57 publications
1
41
0
Order By: Relevance
“…The estimated phosphite deposition flux from WACCM‐P is then 1 × 10 −9 g m −2 yr −1 , with a maximum of 5 × 10 −9 g m −2 yr −1 . This global mean flux is close to the geometric mean of the recent estimate of phosphite production from lightning strikes of between 100–10,000 kg annually (Hess et al., 2021). Moreover, the phosphate within MSPs, which are mostly less than 100 nm in radius (Bardeen et al., 2008; Brooke et al., 2017), will be even more prone to lightning‐initiated reduction, or aqueous phase chemistry during their residence in the highly acidic Junge layer (Saunders et al., 2012), than the phosphate buried within much larger meteorites.…”
Section: Discussionsupporting
confidence: 83%
“…The estimated phosphite deposition flux from WACCM‐P is then 1 × 10 −9 g m −2 yr −1 , with a maximum of 5 × 10 −9 g m −2 yr −1 . This global mean flux is close to the geometric mean of the recent estimate of phosphite production from lightning strikes of between 100–10,000 kg annually (Hess et al., 2021). Moreover, the phosphate within MSPs, which are mostly less than 100 nm in radius (Bardeen et al., 2008; Brooke et al., 2017), will be even more prone to lightning‐initiated reduction, or aqueous phase chemistry during their residence in the highly acidic Junge layer (Saunders et al., 2012), than the phosphate buried within much larger meteorites.…”
Section: Discussionsupporting
confidence: 83%
“…[#29 -Lightning minerals]: A small suite of 9 highly-reduced minerals, including silicon metal, graphite, iron, moissanite, and schreibersite, is associated with the production of fulgurites by lightning strikes (Essene and Fisher 1986;Grapes 2006;Pasek et al 2012;Hess et al 2021). Pasek and Block (2009) suggested that lightning-induced This is the peer-reviewed, final accepted version for American Mineralogist, published by the Mineralogical Society of America.…”
Section: Systematic Survey Of Paragenetic Modesmentioning
confidence: 99%
“…DOI: https://doi.org/10.2138/am-2022-8099. http://www.minsocam.org/ reduction of phosphate minerals might have provided a source of biologically useful P compounds prior to life's origins -an idea amplified by Hess et al (2021).…”
Section: Systematic Survey Of Paragenetic Modesmentioning
confidence: 99%
“…1-10% of the early Earth crust was composed by phosphide minerals. 14 Very recently, Hess et al 15 proposed a new route to provide available phosphorus on the early Earth through lighting strikes as a major facilitator of prebiotic phosphorus reduction. Indeed, lighting strike hitting clay-rich soil of the early crust will form highly reduced glasses called fulgurites, in which schreibersite is synthesized in situ by the high energy provided during the electric discharge.…”
Section: Introductionmentioning
confidence: 99%